Long-Term Results of Reconstruction with Pelvic Allografts after Wide Resection of Pelvic Sarcomas - Mehmet Ayvaz; Senol Bekmez; M. Ugur Mermerkaya; Omur Caglar; Emre Acaroglu; A. Mazhar Tokgozoglu (The Scientific World Journal)
Reconstruction after the resection of a pelvic tumor is a challenging procedure in orthopedic oncology. The main advantage of allograft reconstruction is restoration of the bony architecture of the complex pelvic region. However, high complication rates such as infection and allograft resorption had been reported in the literature. In this study, we aimed to retrospectively review nine patients treated with pelvic resection and structural pelvic allograft reconstruction. Functional results, complications, and survival of the patients and the allografts were evaluated. At a mean follow-up of 79 months, three patients were dead. Major complications were detected in eight of the nine patients. Infection (four of the nine patients) and allograft resorption (three of the nine patients) were the most common causes of failure. The cumulative survival of the patients was 66.7 percent at 70 months. However, allograft survival was only 26.7 percent at 60 months. Mean MSTS score was 69. In conclusion, we suggest that other reconstruction options should be preferred after pelvic resections because of the high complication rates associated with massive allograft reconstruction.